Pulmonary Hypertension in Systemic Lupus Erythematosus with Raynaud’s Phenomenon: Case Report - Agnes Dina Irene Dorithy Zagoto; Ayu Paramaiswari (Indonesian Rheumatology Association, 2021)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that affects multiple organs such as skin, joints, kidneys, heart, lungs, nervous system and blood. Pulmonary hypertension is a rare complication of SLE.1 Systemic lupus erythematosus associated with pulmonary hypertension was defined as an increase in the average pressure in the pulmonary artery at rest ? 25 mmHg with pulmonary capillary wedge pressure ?15 mm Hg and an increase in pulmonary vascular resistance.2 The prevalence of pulmonary hypertension in SLE approximately 0.5 to 17.5%. Predictors factors of the occurrence of pulmonary hypertension in LES is Raynaud's phenomenon, anti-U1RNP antibody, and antibody positive anticardiolipin.3 A woman aged 37 years came with a chief complaint of pain in the fingers and toes with black-colored wounds felt since 6 months before admission. From the anamnesis, physical examination, support to meet 5 of the classification criteria for systemic lupus erythematosus based on the 1997 ACR criteria which includes manifestations of arthritis, mucocutaneous, serositis, lupus antiokoagulan, and ANA IF positive. In these patients also found the typical signs and symptoms of Raynaud's phenomenon which leads to the symptoms of pain in the fingers of both hands when exposed to cold and pale to red when heated and has been confirmed from the results of arteriography. From the results of echocardiography reveal any pulmonary hypertension. This patient was treated with steroids, immunosuppressants and antiplatelet. The case was removed because of pulmonary hypertension is a complication LES rare and necessary sharpness in diagnosis. Patients with pulmonary hypertension of unknown or untreated can become a progressive right heart failure and lead to death.3